Od kod priimek Tulščak? - Šivic-Dular, Alenka (Slavistična revija, 1984)
The Slovene Protestant writer Janž Tulščak's surname is reconstructed as *Tolščak and interpreted to be derived from the place name Tolsti Vrh
Keywords: etimologija; onomastika; priimki; slovenščina; Tulščak, Janž